Demonetisation : the economists speak - Uma Kapila , ed (Academic Foundation, 2017)
Demonetization has come to describe in India one economic decision that shook a billion people from the very moment it was announced by Prime Minister Narendra Modi on 8th November 2016; from the manifestation shrouded in secrecy, the rationale, the aftermath, the short and the long term economic impact, the social and political fallout, and much more. Endless animated discussions in virtually every kind of group at any kind of place, unending serpentine queues at banks and ATMs, continuous news headlines for days and weeks, countless speeches, reactions and counter-arguments, a stalled parliament—India’s recent demonetization has indeed unfolded at an unprecedented scale. Amidst the din and cacophony, it makes a lot of sense to make available to the reader, a bunch of authentic writings by noted economists/scholars, and policymakers on how they view demonetisation.